Filozofia informatyki – młoda dyscyplina z długą historią - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
In this publication R. Murawski's anthology of philosophy of computing was reviewed. This review shows that this branch of philosophy is considered as quite new, but it has a long history. Murawski's book is a very good introduction to philosophy of computing - both for IT professionals and students of philosophy.